The Influencial Factors on Counselling Effectiveness Using Decision-Making Tools in Selecting Long-Term Contraceptive Methods in Kendal District - Sundari, Ana; Murti, Bhisma; Sutrisna, Endang (Indonesian Journal of Medicine, 2017)
Background: One of the efforts to increase the usage of Long-term Contraceptive Methods is an effective counselling using decision-making tools. This counselling is very important to assist acceptors in making decisions and providing convenience to problem solving, behaviour changes or attitudes towards contraception. This study aimed to analyse the counselling effectiveness using decision-making tools in selecting methods of long-active reversible contraception.Subjects and Method: This was an analytic observational study with case-control design. This study was conducted at District of Kendal, Central Java, from May 18 to August 18, 2016. Population of this study was the entire contraceptive acceptors who were at district of Kendal. The samples were as much as 100 people, 35 contraceptive acceptors in case group and 65 in control group using quota sampling technique. The exogenous variables were counselling on Decision-Making Tools, self-efficacy, subjective norms, behaviour of women of reproductive age, ages of women of reproductive age, parity of women of reproductive age, levels of education of women of reproductive age. The endogenous variables were the usage of long-term contraÃÂceptive methods. The data were collected by a set of questionnaires and analyzed by path analysis.Results: AgeÃ¢â°Â¥35 years old (b=-2.19; CI 95%=-3.60 to -0.77; p=0.002), multiparity (b=-2.04; CI 95%=-3.99 to -0.09; p=0.040). Primary education level(b=-0.55; CI 95%=0.12 to 1.85; p= 0.359). There was a positive correlation between counselling and behaviour (b=0.98; CI 95%=0.12 to 1.85; p=0.025). There was a correlation between counselling and efficacy (b=1.56; CI 95%=0.62 to 2.50; p= 0.001). There was a correlation between behaviour and participation in the long-term contraceptive methods (b=4.02; CI 95%=1.71 to 6.34;p=0.001). There was a correlation between self-efficacy and participation in the long-term contraceptive methods (b=3.23; CI 95%=0.71 to 5.75; p=0.012). There was a correlation between subjective norms and participation in the long-term contraceptive methods (b=3.25; CI 95%=0.92 to 5.59; p=0.006).Conclusion: Counselling using decision-making tools influences behaviour and self-efficacy in using the long-term contraceptive methods indirectly. Keywords: long-term contraceptive methods, counselling, decision-making toolsCorrespondence:ÃÂ Ana Sundari. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: ana.sundari@yahoo.com.Journal of Medicine (2017), 2(1): 10-20https://doi.org/10.26911/theijmed.2017.02.01.02